Temperature dependence of the surface plasmon resonance in small electron gas fragments, self consistent field approximation. (July 2017) - Fasolato, C.; Sacchetti, F.; Tozzi, P.; Petrillo, C.
Abstract: The temperature dependence of the surface plasmon resonance in small metal spheres is calculated using an electron gas model within the Random Phase Approximation. The calculation is mainly devoted to the study of spheres with diameters up to at least 10 nm, where quantum effects can still be relevant and a simple plasmon pole approximation for the dielectric function is no more appropriate. We find a possible blue shift of the plasmon resonance position when the temperature is increased while keeping the size of the sphere fixed. The blue shift is appreciable only when the temperature is a large fraction of the Fermi energy. These results provide a guide for pump and probe experiments with a high time resolution, tailored to study the excited electron system before thermalisation with the lattice takes place. Abstract : Highlights: Dielectric function calculation of small electron gas fragments (RPA approximation). Effect of high temperature on optical response of "large" gold nanospheres. Blueshift of surface plasmon resonance at high electronic temperatures. Benchmark for pump-and-probe optical experiments at extreme conditions, as at FELs.